Delta Like-1 Gene Mutation: A Novel Cause of Congenital Vertebral Malformation - Barhoumi, Tlili; Nashabat, Marwan; Alghanem, Bandar; Alhallaj, AlShaimaa; Boudjelal, Mohamed; Umair, Muhammad; Alarifi, Saud; Alfares, Ahmed; Mohrij, Saad A. Al; Alfadhel, Majid (Frontiers in Genetics, 2019)
Skeletal development throughout the embryonic and postnatal phases is a dynamic process, based on bone remodeling and the balance between the activities of osteoclasts and osteoblasts modulating skeletal homeostasis. The Notch signaling pathway is a regulator of several developmental processes, and plays a crucial role in the development of the human skeleton by regulating the proliferation and differentiation of skeletal cells. The Delta Like-1 (DLL1) gene plays an important role in Notch signaling. We propose that an identified alteration in DLL1 protein may affect the downstream signaling. In this article, we present for the first time two siblings with a mutation in the DLL1 gene, presenting with congenital vertebral malformation. Using variable in-silico prediction tools, it was predicted that the variant was responsible for the development of disease. Quantitative reverse-transcription polymerase chain reaction for the Notch signaling pathway, using samples obtained from patients, showed a significant alteration in the expression of various related genes. Specifically, the expression of neurogenic locus notch homolog protein 1, SNW domain-containing protein 1, disintegrin and metalloproteinase domain-containing proteins 10 and 17, were upregulated. In contrast, the expression of HEY1, HEY2, adenosine deaminase, and mastermind-like-1 was downregulated. Furthermore, in a phosphokinase array, four kinases were significantly changed in patients, namely p27, JANK1/2/3, mitogen- and stress-activated protein kinases 1 and 2, and focal adhesion kinase. Our results suggest an implication of a DLL1 defect related to the Notch signaling pathway, at least in part, in the morphologic abnormality observed in these patients. A limitation of our study was the low number of patients and samples. Further studies in this area are warranted to decipher the link between a DLL1 defect and skeletal abnormality.